Two new species of the genus Elattoma (Acari: Heterostigmatina: Pygmephoridae) phoretic on Morimus verecundus (Coleoptera: Cerambycidae) from Iran - Rahiminejad, Vahid; Hajiqanbar, Hamidreza; Fathipour, Yaghoub (Zootaxa, 2011)
Two new species of the genus Elattoma Mahunka, 1969 (Acari: Heterostigmatina: Pygmephoridae) associated with Morimus verecundus (Faldermann 1836) (Coleoptera: Cerambycidae) are described and illustrated from Oak forests in Golestan province, Northern Iran: Elattoma cerambycidum Rahiminejad & Hajiqanbar sp. nov. and E. abeskoun Rahiminejad & Hajiqanbar sp. nov. Both formed large colonies attached on the ventral surface, around coxae I–III of different individuals of the host beetles. This is the first phoretic record of the genus Elattoma for beetles of the family Cerambycidae. Furthermore, our record of Elattoma is new for the arthropod fauna of Iran. A key to world species of the genus Elattoma is also provided.